One-stage transanal Swenson procedure for rectosigmoid Hirschsprung's disease in infants and children. Issue 3 (July 2016) - Al-Baghdady, Ayman A.; El-Shafei, Ehab A.; El-Asmar, Khaled M.
Abstract : Objective: This study aimed to present the outcome of transanal one-stage Swenson pull-through procedure in the management of rectosigmoid Hirschsprung's disease (HD). Background: HD is a common cause of intestinal obstruction in pediatric age. Several pull-through procedures have been used to treat this pathology. Patients and methods: Between June 2008 and June 2015, 84 children with biopsy-proven HD underwent transanal one-stage Swenson pull-through procedure. Intraoperative details, postoperative complications, and bowel habits were recorded. Follow-up period ranged from 6 to 42 months. Results: The age at the time of surgery ranged from 3 months to 2 years. The length of the resected aganglionic segment ranged from 12 to 34 cm. The operating time ranged from 72 to 180 min. Postoperative hospital stay ranged from 3 to 6 days. There were no anastomotic leaks, no perianal infection, or postoperative bowel obstruction. Twelve patients (14.28%) developed postoperative enterocolitis. Six patients (7.14%) required a posterior internal sphincter myectomy despite repeated dilatations. All patients had less than four times bowel motions per day, 3 months after surgery. No voiding disturbances were encountered at the end of the follow-up period and none of the patients complained of recurrent constipation. Six patients developed perianal dermatitis, which was treated conservatively within 3 months after surgery. Anastomotic circumference could not be felt at digital examination in 78 patients 3 months after surgery. Conclusion: One-stage transanal Swenson pull-through procedure is a safe alternative and simpler procedure for rectosigmoid HD with low morbidities and accepted outcome as regards postoperative bowel habits.